Fenced In: Intimacy and Mobility in Highlands Papua New Guinea. Issue 1 (23rd April 2013) - Maclean, Neil
Abstract This paper is organised around the analysis of an 'event'; a truck trip from Kwima, a Maring speaking settlement in the Western Highlands of Papua New Guinea, to Banz in the Wahgi Valley and an evening spent on the road. The event forms a standpoint from which to assess the impact of the decline of civic space, and faltering legacy of colonial governmentality, in the Jimi since 1980. I describe the emergence of new forms of mobility based around the nexus between local forms of business and trucks. In particular I focus on new and anxious forms of masculine inside relationships, understood as a transformation of a habitus of intimacy, round which such mobility is built. I argue that this transformation should be understood in terms of the dialectical relationship between business as an expansive profit oriented project on the one hand, and its anchoring in clan defined space on the other. At the same time the event provides a vantage point to reflect on the nature of long‐term fieldwork, the methodological significance of the subjectivity of the ethnographer, and the nature of ethnographic error.